2021
DOI: 10.1007/s00066-021-01831-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy with low-energy x-rays after neurosurgical resection of brain metastases—an Augsburg University Medical Center experience

Abstract: Purpose External-beam radiotherapy (EBRT) is the predominant method for localized brain radiotherapy (LBRT) after resection of brain metastases (BM). Intraoperative radiotherapy (IORT) with 50-kV x‑rays is an alternative way to focally irradiate the resection cavity after BM surgery, with the option of shortening the overall treatment time and limiting normal tissue irradiation. Methods We retrospectively analyzed the outcomes of all patients who u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…The estimated 1-year LC, DBC and OS were 84.3%, 33.5% and 61.6%, respectively. RN was observed in one patient and four patients developed LMD over the course the disease [30]. Based on these studies, Lex-IORT seems to be effective and safe regarding LC and RN rates, comparable to historical hFSRT data.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The estimated 1-year LC, DBC and OS were 84.3%, 33.5% and 61.6%, respectively. RN was observed in one patient and four patients developed LMD over the course the disease [30]. Based on these studies, Lex-IORT seems to be effective and safe regarding LC and RN rates, comparable to historical hFSRT data.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, low-energy X-ray intraoperative RT (lex-IORT) is gaining attention: surgical resection and RT performed within one procedure seems to be convenient regarding the duration of total treatment; at the same time, challenges of optimal target delineation for postsurgical cavities for external beam radiation therapy (EBRT) can be resolved [28]. Several studies have demonstrated effectiveness and safety with good local control rates up to 88% at 12 months [29][30][31]. This study is a retrospective descriptive single center analysis with a report of the first experience with lex-IORT for the management of BM at the Technical University of Munich (TUM) Medical Center in Munich, Germany (School of Medicine).…”
Section: Introductionmentioning
confidence: 99%
“…LMD occurred in 3% of patients, and RN occurred in 7% of patients. Kahl et al reported their cohort of 40 patients with 44 resected metastases, who were treated with LEX-IORT using a median dose of 20Gy (66). Median overall survival was 26.4 months (1year survival of 61.6%), and the local control was 88.6% (1-year local control of 84.3%).…”
Section: Intraoperative Radiotherapymentioning
confidence: 99%
“…Computational preoperative planning of surgical interventions entails multiple benefits, in particular reduced risk to the patient and shorter interds, computational preoperative planning has seen success in applications such as radiotherapy Calvo et al (2014) , neurosurgery Prada et al (2014) ; Kahl et al (2021) ; Nemoto et al (2002) , or orthognathic surgery Alcañiz et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…IORT delivers a large dose of ionizing radiation to the tumor bed during surgery, thus maximizing the dose applied to the tumor while minimizing the dose applied to nearby healthy tissue. Preoperative planning of IORT involves calculation of a cumulative dose on a volume image that faithfully represents the patient’s anatomy, and is successfully used in, e.g., neurosurgery Prada et al (2014) ; Kahl et al (2021) ; Nemoto et al (2002) . However, to date IORT is hardly possible on breast cancer surgery, due to the strong mismatch between preoperative and intraoperative settings.…”
Section: Introductionmentioning
confidence: 99%